Synthesis and characterization of fluorine-containing C60 derivatives and their charge transfer photophysics in organic photovoltaics - Larson, Bryon W., author; Strauss, Steven H., advisor; Rumbles, Garry, advisor; Rappé, Anthony, committee member; Bartels, Randy, committee member; Chen, Eugene, committee member; Robinson, Raymond S., committee member (Colorado State University. Libraries, 2013)
Transformative advances in the science of new materials and technological solutions for energy conversion and storage require focused efforts from scientists across different disciplines. One of the major frontiers for modern chemistry is the molecular design of advanced materials from earth-abundant elements with finely tuned chemical, photophysical, and electronic properties. In this work, several highly efficient and, in some cases, highly regioselective synthetic methodologies have been developed for the first time that resulted in a wide array of versatile fullerene-based organic electron acceptors with highly tunable electronic properties. The classes of these newly synthesized and characterized materials include mono-perfluorocarbocyclic C60 derivatives, highly functionalizable ω-X-perfluoroalkylfullerenes (X = SF5, Br, I, COOEt), twenty one new isomers of deca-trifluoromethyl[60]fullerenes, and several new isomers of octa- and hexa-trifluoromethyl[60]fullerenes. Improved synthetic and separation techniques yielding up to multi-gram amounts of difluoromethylene[60]fulleroid and several other classes of technologically important perfluoroalkylfullerenes have also been developed, which enabled several organic photovoltaic-relevant studies using state-of-the art facilities at the National Renewable Energy Laboratory. This included the first experimental determination of an optimal driving force for the relative yield of free carrier generation in a family of polyfluorene polymers by using a series of trifluoromethylfullerene acceptors with a large range of electron affinities synthesized by the author. In another study, a judiciously selected series of acceptors was applied for a time-resolved microwave conductivity (TRMC) study that provided the first compelling experimental evidence that the yield for uncorrelated free charge generation in organic photovoltaic (OPV) device-relevant blends of donor:acceptor active layers is a function of carrier mobility. Finally, a new fullerene acceptor rivaling one of the champion fullerene derivatives, phenyl-C61-butyric acid methyl ester (PCBM), in OPV performance was studied by TRMC and in OPV devices.
Keywords: fluorine; charge generation; organic solar cell; perfluoroalkyl; photovoltaics; Fullerene